2020
DOI: 10.3389/fphys.2020.00748
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain After Spinal Cord Injury: Is There a Role for Neuron-Immune Dysregulation?

Abstract: Spinal cord injury (SCI) is a devastating event with a tremendous impact in the life of the affected individual and family. Traumatic injuries related to motor vehicle accidents, falls, sports, and violence are the most common causes. The majority of spinal lesions is incomplete and occurs at cervical levels of the cord, causing a disruption of several ascending and descending neuronal pathways. Additionally, many patients develop chronic pain and describe it as burning, stabbing, shooting, or shocking and oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 93 publications
0
24
0
2
Order By: Relevance
“…Previous reports have demonstrated that neuropathic pain can accompany SCI [ 40 ]. Here, we confirmed mechanical allodynia using a dynamic plantar test [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have demonstrated that neuropathic pain can accompany SCI [ 40 ]. Here, we confirmed mechanical allodynia using a dynamic plantar test [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical allodynia is only one form of neuropathic pain and the causes of neuropathic pain after SCI are not known, but those suspected include immune responses, glial cells, and myelin degeneration [ 40 , 42 , 43 , 44 ]. Here, we confirmed an inflammatory response using the markers CD68 and IL-1β ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have argued that Nep is attributed to a dysregulation and hyperexcitability of primary afferent pathways (6). However, recent evidence suggests that neuroinflammation may also be involved in Nep after SCI (7). The activation of microglia is thought to contribute to the maintenance of Nep post-SCI (8).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have argued that Nep is attributed to a dysregulation and hyperexcitability of primary afferent pathways [6]. However, recent evidence suggests that neuroin ammation may also be involved in neuropathic pain after SCI [7]. The activation of microglia is thought to contribute to the maintenance of Nep post-SCI [8].…”
Section: Introductionmentioning
confidence: 99%